2018
DOI: 10.1111/cge.13223
|View full text |Cite
|
Sign up to set email alerts
|

Lack of clear and univocal genotype‐phenotype correlation in familial Mediterranean fever patients: A systematic review

Abstract: Familial Mediterranean fever (FMF) is the most common autosomal recessive autoinflammatory disease. To date, following the isolation of more than 280 MEFV sequence variants, the genotype-phenotype correlation in FMF patients has been intensively investigated; however, an univocal and clear consensus has not been yet reached. Thus, the aim of this systematic review was to analyze the available literature findings in order to provide to scientific community an indirect estimation of the impact of genetic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 79 publications
(220 reference statements)
7
48
3
1
Order By: Relevance
“…The current consensus classifies this variant as benign. 48 Functional evaluation in the ex vivo colchicine assay showed that the R202Q Pyrin variant responded similarly to wild-type Pyrin. Furthermore, unlike patients with classical FMF mutations, none of the R202Q-bearing patients in our study benefitted from colchicine therapy (see online supplementary table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current consensus classifies this variant as benign. 48 Functional evaluation in the ex vivo colchicine assay showed that the R202Q Pyrin variant responded similarly to wild-type Pyrin. Furthermore, unlike patients with classical FMF mutations, none of the R202Q-bearing patients in our study benefitted from colchicine therapy (see online supplementary table 1).…”
Section: Discussionmentioning
confidence: 99%
“…P369S is an exon 3 variant for which limited genetic and clinical data are currently available. 48 The variant can be present by itself or as part of a complex (E148Q-P369S-R408Q) 49 Autoinflammatory disorders patient cohort. Similar to E148Q and R202Q, P369S is highly common (2%-3% of the overall population) and is therefore to be rather considered a polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there are overlapping symptoms among FMF and a number of polygenic autoinflammatory diseasesincluding periodic fever, aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome, systemic-onset juvenile idiopathic arthritis (sJIA), and Behçet diseaseit is often challenging to make a purely clinical diagnosis of FMF. This is particularly the case in regions such as North America where FMF is rare and may be milder or present atypically [11,12]. Some patients may also be mistakenly diagnosed with autoinflammatory or autoimmune syndromes that have some overlapping clinical features, including Behcet disease, systemic lupus erythematosus, or rheumatic fever [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic mutations have been described for diagnosing FMF. Of these, the M694V mutation is most common in Turkish patients with FMF and is associated with an aggressive phenotype of the disease . Accordingly, we found the M694V mutation to be most common in our FMF patients (62%), followed by the M680I and V726A mutations.…”
Section: Discussionmentioning
confidence: 52%
“…Of these, the M694V mutation is most common in Turkish patients with FMF and is associated with an aggressive phenotype of the disease. 12,13 Accordingly, we found the M694V mutation to be most common in our FMF patients (62%), followed by the M680I and V726A mutations. The frequency of FID in patients with homozygous M694V mutation was 64%, and the frequency of AID in those with heterozygous M694V mutation was 77%.…”
Section: Discussionmentioning
confidence: 61%